Laparoscopic biopsy-proven lupus nephritis in autosomal dominant polycystic kidney disease - Ji In Park; Hajeong Lee; Jung Nam An; Ho Jun Chin; Suhnggwon Kim (The Korean Society of Nephrology, 2012)
A 48-year-old woman with autosomal dominant polycystic kidney disease (ADPKD) presented with generalized edema and arthralgia. She showed evidences of acute glomerulonephritis including nephrotic-ranged proteinuria. Because her serologic test results were consistent with those for systemic lupus erythematosus (SLE), we performed laparoscopic renal biopsy that confirmed World Health Organization (WHO) class IV lupus nephritis. She was treated with steroids and intravenous cyclophosphamide pulse therapy and eventually started hemodialysis 8 years after the lupus nephritis was diagnosed. To our knowledge, this is the first case wherein a patient with ADPKD underwent a laparoscopic biopsy for diagnosing lupus nephritis.